"PROPAGANDISTS FOR THE BEHAVIORAL SCIENCES": THE OVERLOOKED PARTNERSHIP BETWEEN THE CARNEGIE CORPORATION AND SSRC IN THE MID‐TWENTIETH CENTURY. Issue 2 (3rd March 2016) - HAUPTMANN, EMILY
Abstract : The Carnegie Corporation's role as a patron of the behavioral sciences has been overlooked; its support for the behavioral sciences not only began earlier than the Ford Foundation's but was also at least equally important to their success. I show how the close postwar collaboration between the Carnegie Corporation and the Social Science Research Council (SSRC) to promote the behavioral sciences emerged after a strugglebetween Carnegie and the Rockefeller Foundation over the direction and leadership of the SSRC. I then focus on three postwar projects Carnegie helped conceive and fund that were publicized as the work of the SSRC: Chase's The Proper Study of Mankind (1948), Stouffer et al.'s The American Soldier (1949, 1950 ), and the Michigan's Survey Research Center 1952 election study. In each of these projects, Carnegie deliberately muted its own role and promoted the remade SSRC as a major advocate for the behavioral sciences.